2013
DOI: 10.1007/s00018-013-1268-6
|View full text |Cite
|
Sign up to set email alerts
|

RIAM (Rap1-interacting adaptor molecule) regulates complement-dependent phagocytosis

Abstract: Phagocytosis mediated by the complement receptor CR3 (also known as integrin αMβ2 or Mac-1) is regulated by the recruitment of talin to the cytoplasmic tail of the β2 integrin subunit. Talin recruitment to this integrin is dependent on Rap1 activation. However the mechanism by which Rap1 regulates this event and CR3-dependent phagocytosis remains largely unknown. In the present work we examined the role of the Rap1 effector RIAM, a talin binding protein, in the regulation of complement-mediated phagocytosis. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
53
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 39 publications
5
53
0
Order By: Relevance
“…Analysis of the respiratory burst in response to tumor necrosis factor-a (TNF-a) revealed a reduction in free reactive oxygen species (ROS) production in RIAM −/− PMNs, pointing to a role of RIAM in b 2 integrin-mediated outside-in signaling (83). These results are in accordance with data obtained from RIAM KD human promyelocytic cells and indicate an essential role of RIAM in b 2 integrin-mediated phagocytosis (82).…”
Section: −/−supporting
confidence: 80%
See 4 more Smart Citations
“…Analysis of the respiratory burst in response to tumor necrosis factor-a (TNF-a) revealed a reduction in free reactive oxygen species (ROS) production in RIAM −/− PMNs, pointing to a role of RIAM in b 2 integrin-mediated outside-in signaling (83). These results are in accordance with data obtained from RIAM KD human promyelocytic cells and indicate an essential role of RIAM in b 2 integrin-mediated phagocytosis (82).…”
Section: −/−supporting
confidence: 80%
“…In accordance with the defective acquisition of the a M b 2 high-affinity state, this study showed that RIAM knockdown reduced complementdependent phagocytosis in response to LPS or f MLP treatment as compared to control cells (82). Moreover, the reduction of a M b 2 activation and impaired phagocytosis in RIAM KD cells was observed even when Rap1 was activated with 8-(4-chlorophenylthio)adenosine 3',5′-cyclic monophosphate (8-CPT-cAMP), a cAMP analog that specifically activates the Rap1-guanine nucleotide exchange factor exchange nucleotide protein directly activated by cAMP (EPAC).…”
Section: Complement-mediated Phagocytosissupporting
confidence: 76%
See 3 more Smart Citations